Alkali‐free processing of advanced open‐celled sinter‐crystallized glass‐ceramics. (17th May 2021) - Elsayed, Hamada; Rabelo Monich, Patricia; Savio, Gianpaolo; Hartmann, Malte; Boccaccini, Aldo R.; Galusek, Dusan; Kraxner, Jozef; Bernardo, Enrico
Abstract: The cooling of a melt corresponding to the eutectic between wollastonite (CaSiO3 ) and diopside (CaMgSi2 O6 ) determines the synthesis of an interesting example of alkali‐free bioactive glass, easily converted into glass‐ceramics featuring two silicate phases, coupled also with åkermanite (Ca2 MgSi2 O7 ), by sinter‐crystallization of fine glass powders at 1000°C. The fabrication of scaffolds by digital light processing of glass powders suspended in a photo‐curable, sacrificial binder, is a well‐established technique; the present paper aims at disclosing novel approaches, concerning the topology of scaffolds, offering components with remarkable strength, especially in bending conditions. As an alternative, glass‐ceramic foams were fabricated by the firing of porous precursors derived from the gelation of suspensions of glass powders in alkali‐free basic aqueous solution.